Genomic Selection Module 3.0a: Why use genomic selection? Part 1 - Sneller, C. (International Livestock Research Institute, 2017)
Part 3a in a series of eight training modules on Genomic Selection. The modules are prepared by the Clay Sneller, lead plant breeder at the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI Hub), in Nairobi